Magnetic Proximity Effect in Graphene/CrBr3 van der Waals Heterostructures. Issue 16 (4th March 2020) - Tang, Chaolong; Zhang, Zhaowei; Lai, Shen; Tan, Qinghai; Gao, Wei‐bo
Abstract: 2D van der Waals heterostructures serve as a promising platform to exploit various physical phenomena in a diverse range of novel spintronic device applications. Efficient spin injection is the prerequisite for these devices. The recent discovery of magnetic 2D materials leads to the possibility of fully 2D van der Waals spintronics devices by implementing spin injection through the magnetic proximity effect (MPE). Here, the investigation of MPE in 2D graphene/CrBr3 van der Waals heterostructures is reported, which is probed by the Zeeman spin Hall effect through non‐local measurements. Quantitative estimation of the Zeeman splitting field demonstrates a significant MPE field even in a low magnetic field. Furthermore, the observed anomalous longitudinal resistance changes at the Dirac point R XX, D with increasing magnetic field near ν = 0 may be attributed to the MPE‐induced new ground state phases. This MPE revealed in the graphene/CrBr3 van der Waals heterostructures therefore provides a solid physics basis and key functionality for next‐generation 2D spin logic and memory devices. Abstract : The magnetic proximity effect (MPE) in 2D graphene/CrBr3 van der Waals heterostructures is probed by the Zeeman spin Hall effect via non‐local transport measurements; estimation of the Zeeman splitting energy demonstrates a significant magnetic proximity exchange field. The newly observed anomalous longitudinal resistances at the Dirac point with magnetic field may be attributed to the new phases of the ground state induced by MPE.